Association Between Maternal Serum Total Oxidant Status Total Antioxidant Status and Preterm Labor: A Prospective - Controlled Clinical Study - Kalaycı, Hakan; Uğur, Mete Gürol; Öztürk, Ebru; Balat, Özcan; Erel, Özcan (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: To measure the levels of individual antioxidant components of pregnants with preterm labor to evaluate their total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI). STUDY DESIGN: Prospectively-controlled 31 pregnants with a diagnosis of preterm labor (group Ι) and 32 controls (group ΙΙ) were evaluated for demographic data, general and obstetrical physical examination, obstetrical sonography, and routine laboratory tests. TAS, TOS and OSI levels were also measured. RESULTS: There was no difference in terms of demographic data, ultrasound and routine laboratory parameters, total oxidant levels, total antioxidant capacity and oxidative stress index between the two groups (p=0.621, p=0.706 and p=0.450, respectively). CONCLUSIONS: Improper balance between TAS and TOS may not be a major issue in the pathogenesis of preterm labor in which infection does not precede. ‘Screening or prediction of preterm labor‘ needs new trials with large populations, particularly concerning enviromental and dietary features of the population.